How to Brush Teeth for Class VI Students at SDN Milangasri 1 Magetan - Dewi, Yanita Almas Chandra; Hidayati, Sri; Edi, Imam Sarwo (SURABAYA DENTAL THERAPIST JOURNAL, 2025)
Problem: high prevalence of permanent first molar caries in students in grades 4, 5, 6 at SDN 1 Candisari, Lamongan Regency. Research objective: to determine the knowledge of permanent first molar tooth caries in students in grades 4, 5, 6 after counseling using rotating wheel media at SDN 1 Candisari, Lamongan Regency. Research method: the type of research used is descriptive research. The research targets were students in grades 4, 5, 6 of SDN 1 Candisari, Lamongan Regency. Data collection was carried out by distributing questionnaires. The data analysis technique used is by adding up the results for each correct answer, then calculating the average (mean) in percentage form and presenting it in table form. Research results: Knowledge of students in grades 4, 5, 6 regarding caries of permanent first molars after using rotating wheel media is included in the sufficient category